The growing field of immunometabolism and exercise: Key findings in the last 5 years - Padilha, Camila S. [UNESP]; Morano, Ana E. Von Ah [UNESP]; Krüger, Karsten; Rosa-Neto, José C.; Lira, Fabio S. [UNESP] (Wiley, 2022)
This perspective review highlights the impact of physical exercise on immunometabolic responses in the past 5 years. Understanding immunometabolism as a part of immunological research is essential. Furthermore, the roles of both acute and chronic effects of physical exercise on health, aging, and chronic diseases in immunometabolic changes should be elaborated. In immune cells, β2 adrenergic signaling stimulates the preferential mobilization of inflammatory phenotypes, such as CD16+ monocytes and CD8+ T cells, into the bloodstream after a physical exercise session. The mobilization of immune cells is closely related to the availability of energetic substrates for the cell and mechanisms associated with the uptake and oxidation of fatty acids and glucose. These cells, especially senescent T cells, are mobilized to the peripheral tissues and undergo apoptotic signaling, stimulating the creation of a “vacant space” where new cells will be matured and replaced in the circulation. This results in the upregulation of the expression and secretion of anti-inflammatory cytokines (IL-10 and IL-1ra), leading to increased regulatory immune cells that provide immunoregulatory properties. Thus, we suggest that a significant nutrient available to the cell will favor oxidative metabolism, augment ATP production, and consequently maintain the immune cells in their quiescent state, as well as promote rapid activation function. Therefore, based on the studies discussed in this perspective review, we highlight the importance of performing moderate-intensity continuous and high-intensity intermittent aerobic exercises, due to a higher magnitude of energetic demand and release of anti-inflammatory cytokines (IL-6 and IL-10).
Keywords: exercise; immune system; immunometabolic response; metabolic pathway